Diseño de un sistema de anclaje para un tractor con malacate. - Rincón C., Carlos J. (Instituto Colombiano Agropecuario, 2019)
This project deals with the design of a winch sprag for the Spider tractor developed at tha National College of Agricultural Engineering in an attempt to provide a cheap source of mechanical power for small farmers of developing countries. Basic sprag design aims at abtaining high pull forces from relatively low mass machines. An attempt was made to create a perfectly rough interfase at the sprag thus maximising the draught force required for soil failure. The position of the sprag was determined by considering longitudinal stabilitj. The experimental results show that soil failure may occur at a lower value of draught than predicted by means of Reece's Fundamental soil Mechanics equation. A simple explanation is that the soil forming the interfase has been disturbed during the first stage of sprag penetration. l-lowever. high pulls were achieved with the sprag utilizing the perfectly rough interface theory.